Le Græculus et la Chananéenne : Salammbô, le roman des traductions - Agnès Bouvier (Flaubert: Revue Critique et Génétique)
Salammbô starts with a translation, that is, a treason. When Hannon comes to harangue the mercenaries billeted in Sicca, Spendius the Greek twists the General’s words and causes the war to unleash. Thus he establishes himself as the master of all the nations of the army that he alone can understand and dominate. Throughout the novel he uses his linguistic ability to generate violence. The translatio in Salammbô is the captatio: civilization working for barbarity. The other translating character in the novel, the heroine herself, practices translation like the art of seduction, until Flaubert, in a writing act that genetic analysis of the drafts can trace, casts on this novel and on its character Babel’s curse, more severe than Tanit’s. Salammbô is the story of a meaning that ceases to circulate, as it is cut, strangled, frozen in the dead interpreters’ mouths.